Risk Analysis of Waterlogging under Combination of Short-duration Heavy Rainfall and Tidal Level in Foshan City - YANG Fan; XU Liang; HAN Jing (Renmin Zhujiang)
With the rapid development of the urban agglomerations in the Guangdong-Hong Kong-MacaoGreater Bay Area, urban waterlogging has drawn great attention from society and scholars. In orderto explore the probability of waterlogging risks in a specific city and provide scientific basisfor the study of urban waterlogging risks in the Pearl River Delta region, from the perspective ofthe causes of waterlogging, this paper takes Foshan as a typical research area, systematicallyanalyzes the probability of encountering storms and high tide levels, constructs a probabilisticmodel for the risk of encounter of rainstorm and high tidal level in urban area of Foshan, andquantitatively evaluates the encounter probabilities and change trend under multiple combinationsof rainstrom and tidal levels in urban area of Foshan by the time-series trend analysis, stormfrequency change statistics, sequence wavelet analysis, and Copula function. The study shows thatsince 2000, the number of rainstorms in urban area of Foshan increased, and the encounterprobability of rainstorm and high tidal level was high, so the risk probability was high. Theresults can provide an important scientific basis for urban flood control and drainage.